2016
DOI: 10.1111/joop.12153
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership and followers' in‐role and extra‐role performance: The mediating role of followers' learning goal orientation

Abstract: This study examined whether and why authentic leadership predicts followers' performance. We hypothesized that authentic leadership predicts followers' learning goal orientation (goal to develop and improve), which, in turn, predicts followers' in-role and (civic virtue) extra-role performance. A multilevel, multisource, time-lagged study, conducted in telecommunications companies in Pakistan, among 115 supervisors and 345 reports supported indirect relations between authentic leadership and (1) follower in-ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…First, self-awareness refers to one’s awareness about his strength and weakness, desires, and cognitions 29 and the leaders’ inclination to improve social interactions with their followers. 30 Second, relational transparency refers to openly sharing one’s feelings and motives and admitting mistakes. The leaders show their true self to their subordinates which helps in building trust, cooperation, and fosters team work among them.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…First, self-awareness refers to one’s awareness about his strength and weakness, desires, and cognitions 29 and the leaders’ inclination to improve social interactions with their followers. 30 Second, relational transparency refers to openly sharing one’s feelings and motives and admitting mistakes. The leaders show their true self to their subordinates which helps in building trust, cooperation, and fosters team work among them.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Communal sharing implies showing care and concern for other members and fulfilling their needs. 41 So, the communal sharing mental schemas can be highly linked with authentic leadership as the authentic leaders have the ability to enhance social interaction with their followers 30 and show concern for others by being unbiased and gain accurate information before reaching any final decision. Moreover, the authentic leaders are transparent in showing their true self to subordinates which assists in enhancing cooperation, building trust, and fostering team work among them.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Using Pakistani samples, research has indicated that authentic leadership accounts for followers’ in‐role and extra‐role performance through learning goal orientation (Mehmood et al. ).…”
mentioning
confidence: 99%
“…Using Chinese samples, studies have provided evidence for the claim that employees who perceive authentic leadership are likely to show high degrees of interactional justice, and as a result exhibit high levels of task performance, creativity, and organizational citizenship behavior (Li et al 2014). Using Pakistani samples, research has indicated that authentic leadership accounts for followers' in-role and extrarole performance through learning goal orientation (Mehmood et al 2016).…”
mentioning
confidence: 99%
“…The control variables that were adopted in this study were age, sex, marital status, education level, and occupation type, job experience (years), and seniority [15,16].…”
Section: Methodsmentioning
confidence: 99%